استخدام الوسائل الأحجية لترقية سيطرة الطلاب على المفردات - Rahmat Fauzi (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
After the researcher made observations, the researcher found several problems faced by students including students' difficulties in memorizing vocabulary. Therefore the researcher wants to use puzzle media in learning Arabic to make it easier for students to remember and memorize Arabic vocabulary. This study aims: (1) to find out the teaching and learning process of mufradat by using riddles for students at MTsS Keumala (2) to find out how effective the teaching and learning process for mufradat is by using riddles for students at MTsS Keumala. The research method used in this research is Classroom Action Research (CAR). To collect data the researcher carried out observations, pre-tests, post-tests, cycle I tests and cycle II tests. The results of the research in this study were: The post test scores of the students did not reach the KKM with an average score of 55.83, only 2 students passed, while the others did not pass. Furthermore, the researcher taught in cycle I using this media and gave cycle I tests, but there were still students who did not pass with an average score of 65. The researcher continued learning in cycle II by using this media so that student scores reached the KKM with an average score average 74.91. The teaching and learning process using puzzle media at MTsS Keumala is effective and in accordance with the expected score of 74.91 (87.50%) and achieves KKM.